Pertanggung Jawaban Hukum Atas Terjadinya Wanprestasi Dalam Penerapan Perjanjian Sewa Pesawat - Martha Emylia Taurisia; Fauzie Yusuf Hasibuan; Ahmad Muliadi (Jurnal Nuansa Kenotariatan, 2018)
The practice of aircraft lessor company with aircraft lessee company may allow “default” because one party does not fulfill its obligations properly and correctly in accordance with the contents of the aircraft lease agreement the. The method used in this research is normative juridical research supported by empirical juridical research. The data used are secondary data composed of primary law, secondary law materials and materials law tertier. In addition the primary data is also used as the supporter of the legal materials of secondary data. For the data analysis was done with a qualitative analysis of the juridical method. The results showed that PT. Air Born Indonesia’s responsibility to lease aircraft in aircraft lease agreement lease agreement air transportation can be categorized as a reciprocal or bilateral agreement. In this case PT Air Born Indonesia as the holder does not fulfill the obligations as agreed in the agreement for not paying the De Havilland Canada DHC-6/300 Twin Otter MSN 518 PK-BAF registration fee corresponding to the amount rent with a specified time, changing the aircraft without the knowledge of Unity Group Ltd, operating the aircraft not in accordance with the agreement, then it is said to have made a default.